Cartografia de memórias docentes no campo: em busca de novos afetos para estar-sendo professora - Santos, Eliziane Santana dos (2020)
This cartographic research, which we call ‘dissertative planting’, is born of a school memory that I experienced in an elementary school. It all started through the experiment in which it was proposed to follow the bean germination process in a container with moistened cotton. The realization of this experiment caused crossings and some discomfort in my reality of planting beans on the ground every yearin my community. The writing of this research has taken this memory as the power from which the reflections on the notion of experience (from Jorge Larrosa’s writings) and becoming (from Gilles Deleuze as the main inspiration) started. Another concept inspires this research, such as Marcos Vilela Pereira's writings on professorality as a constant and unfinished process. For this reason we chose to conduct this research from an autobiographical perspective, but it is also a collective research, when I join other cartographers to cultivate teachers’ memories. The main purpose of this research is to follow the processes of production of teaching memories, aiming to express professoralities in the field. Data production process took place using narrative interviews as devices/seeds, through which we met to talk about our teaching path and the crossings of previous conversations. The conversations were associated with the production of maps in which we sketched the crossings of the school's physical space in/for our professoralities. These devices were complemented by the sharing of images that produced some crossings in our teaching pathways. The research took place in partnership with two other cartographers, both teachers of DivalFigueiredo Machado Municipal School, located in Santa Rosa community, João Durval Carneiro district, Bahia, Brazil. It is noteworthy that we do not intend to reach answers and conclusions. The power of this ‘dissertative planting’ is in its ability to cultivate other perspectives on our process of being teachers. Thus, we created elements of (trans)formation that became collective through the clues that emerged along the path of this cartography and allowed us, through the sharing of experiences, to reflect on other possibilities of being teacher.